Determinación de Escherichia Coli en carne y piel de cerdo en expendios del Mercado 10 de Noviembre de Guaranda - Carvajal Barragán, Darío Wladimir (2016)
The research was conducted in the city of Guaranda, in the parish Gabriel Ignacio Veintimilla, with the theme "Determination of Escherichia coli in meat and pork skin market outlets November 10, Guaranda" whose objectives were; Identify the hygienic quality of meat and pigskin dare the source and the observation of manipulation, establish the degree of contamination of Escherichia coli in meat and pigskin based on the number of colonies, specify the main causes of contamination during sale of meat and pigskin on the market on November 10 in the city of Guaranda. We proceeded to get information through surveys of the dealers to identify problems in handling and in turn the origin of the meat and pigskin. By obtaining 68 samples of pork and 68 skin samples, we obtained 100% contamination with E. coli, so we make a classification of the degree of contamination of the bacteria to identify the percentage of unacceptable samples for consumption human, finding 71% meat and 72% in skin, thus showing, excessive contamination in meat and pigskin, due to improper handling and ignorance of the origin of the meat sold in the market November 10 the city of Guaranda. Values colias forming units E. coli found in meat samples and pigskin were high, exceeding the acceptable limit for the INEN, which showed an obvious contamination in all meat and skin samples obtained.